MENYALAKAN LENTERA KINERJA PIMPINAN PESANTREN SEBAGAI PEMIMPIN YANG MENGINTEGRASI NILAI AGAMA DAN MORAL - Liqo Mursidah; Siti Aimah (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to analyse in depth the role of a Kiai in fostering motivation and shaping the character of students and education personnel through a humanist and spiritual approach at the Salafiyah Asy-Syafi'iyyah Darul Qur'an Islamic Boarding School. The approach used is qualitative with the type of case study, where data is collected through in-depth interviews, participatory observation, and documentation to capture the dynamics of interactions that take place naturally. Data analysis was conducted using the Miles and Huberman interactive model, including data reduction, data presentation, and verification. Data validity was obtained through triangulation of sources and techniques. The results showed that Kiai is not only a spiritual leader, but also an exemplary figure who is able to touch the emotional and moral aspects of the santri and ustadz through individual attention and consistent coaching. His sincere and exemplary presence is a transformative force that builds a meaningful and inspiring educational climate. This research makes an important contribution to the understanding of value-based leadership in the context of holistic and sustainable pesantren education. Keywords: exemplary, leadership, spirituality, pesantren, motivation.